LEGAL REGULATION OF THE COMPLIANCE SYSTEM: GLOBAL EXPERIENCE AND DOMESTIC PRACTICE - BOBERSKYY, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the normative and legal regulation of the compliance system in domestic legislation and identifies the peculiarities of its international regulation. It was found that among the domestic respondents implementing the compliance system in their operations, 60.71% adhere solely to domestic legislation, 24.43% to the US “Foreign Corrupt Practices Act”, and 14.29% to the UK “Bribery Act”. It has been established that the term “compliance” is increasingly used by domestic business structures and, accordingly, is reflected in various systems of Ukrainian legislation. The term first appeared in domestic legislation in the Resolution of the Board of the National Bank of Ukraine on the “Approval of Methodological Recommendations for Improving Corporate Governance in Banks of Ukraine”. Subsequently, the National Bank of Ukraine defined the term compliance-risk in domestic legislation with the Regulation “On the organization of risk management systems in Ukrainian banks and banking groups”. Additionally, the term 'compliance' is interpreted in various Ukrainian laws, including the “On Capital Markets and Organized Commodity Markets" in the context of commodity markets, the Law of Ukraine “On Financial Services and Financial Companies” compliance in the field of financial services, the Law of Ukraine “On Insurance” in the field of insurance. The “National Revenue Strategy until 2030” defines a number of measures to increase the level of compliance with tax legislation by implementing a tax risk management system, i.e. compliance risks based on the Concept of a risk management system. The Organization for Economic Cooperation and Development and the International Monetary Fund have created a number of methodological and explanatory materials intended for the application of tax compliance by tax administrations. For subjects of entrepreneurial activity, the application of the compliance system has a recommendatory character, which is accompanied by the absence of a single regulatory and legal regulation of the compliance system. The official Diya.Business website offers a number of advisory compliance tools for small and medium-sized businesses, namely the anti-corruption policy, code of ethics/conduct, procurement policy and third-party audits.
Keywords: compliance; compliance system; compliance manager; compliance risk; legal regulation of the compliance system; international regulation of the compliance system